A Virtual Screening Study for Lactate Dehydrogenase 5 Inhibitors by Using a Pharmacophore‐based Approach. Issue 8 (15th June 2016) - Tuccinardi, Tiziano; Poli, Giulio; Corchia, Isacco; Granchi, Carlotta; Lapillo, Margherita; Macchia, Marco; Minutolo, Filippo; Ortore, Gabriella; Martinelli, Adriano
Abstract: Inhibitors of human lactate dehydrogenase 5 ( h LDH5) are promising therapeutic agents against cancer. This enzyme is generally found to be overexpressed in most invasive cancer cells and is linked to their vitality especially under hypoxic conditions. In this study, with the aim of identifying new h LDH5 inhibitors, a receptor‐based pharmacophore modeling approach has been tested and, in order to verify the reliability of the reported approach, the Gold and Platinum database from Asinex were filtered. The top‐ranked compounds were experimentally tested for their h LDH5 inhibition activity and enzymatic assays revealed that, among the ten selected compounds, two proved to inhibit the enzyme activity with K i values in the micromolar range ( K i =33.1–76.7 μM). Abstract :